Assessment of Global Disease Activity in Rheumatoid Arthritis by Patients and Physicians. Issue 7 (October 2015) - Gvozdenović, Emilia; Wolterbeek, Ron; Allaart, Cornelia F.; Brenol, Claiton; Dougados, Maxime; Emery, Paul; Ferraccioli, Gianfranco; van der Heijde, Désirée; Huizinga, Tom WJ; Kay, Jonathan; Martin Mola, Emilio; Moots, Rob J.; et al.
<x xml:space="preserve">Abstract</x> Aim The aim of the study was to compare the differences between patient global disease activity (PtGDA) and physician global disease activity (PhGDA) score within and across 13 countries in the METEOR (Measurement of Efficacy of Treatment in the "Era of Outcome" in Rheumatology) database. Methods Data from METEOR were used to compare PtGDA and PhGDA, scored independently on a 100-mm visual analog scale from 0 (best possible) until 100 (worst possible), in 23, 117 visits in 5709 anonymized patients during the period between 2008 and 2012. Linear mixed models were used to model mean differences between PtGDA and PhGDA in 13 countries (Brazil, Czech Republic, France, Ireland, Italy, Latvia, Mexico, the Netherlands, Pakistan, Portugal, Spain, United Kingdom, and the United States), adjusted for differences in Disease Activity Score in 28 joints (DAS28). Generalized estimating equations were used to model differences (>20 mm) between PtGDA and PhGDA score as the outcome and countries as determinants, adjusted for DAS28. Results Mean difference between PtGDA and PhGDA scores varied by country, from −2 mm (physician scores higher) in Mexico to +14 mm (patient scores higher) in Brazil. "Country" was a significant determinant of the difference between PtGDA and PhGDA scores, independent of differences in DAS28. With the Netherlands as reference, PtGDA and PhGDA scores for individual patients differ significantly in almost all (n = 10) countries, with the exception of France and Spain. Conclusions Differences between patients' and physicians' assessment of GDA vary across the countries. Influence of country must be taken into account when interpreting discordances between the patient's and the physician's assessment of GDA in rheumatoid arthritis.